Paul Maenz Köln : Jahresbericht 1979. - Paul Maenz, Köln (Köln : Paul Maenz, 1980)
Darboven, Hanne ; Barry, Robert ; Feldmann, Hans-Peter ; Kosuth, Joseph ; Pohl, Marianne ; Chia, Sandro ; Clemente, Francesco ; De Maria, Nicola ; Longobardi, Nino ; Paladino, Mimmo ; Tatafiore, Ernesto ; Rutault, Claude ; Toroni, Niele ; Poirier, Anne & Patrick
Duits
boek